IMPLEMENTING THE KWL STRATEGY WITH PICTURES TO IMPROVE STUDENTS' READING COMMANDMENTS - Ni Kadek Suciani; I Ketut Wardana; I Nengah Astawa (Academic Journal on English Studies (AJOES), 2021)
Most students learning English have difficulty identifying general information, specific information, and text meanings and references due to a lack of vocabulary. Therefore, an appropriate and effective teaching strategy should allow students to improve their reading comprehension. The present study attempts to find out the reading comprehension of the eighth-grade students of the SMP Negeri 3 Ubud in the school year 2020/2021 could be improved by the KWL strategy in combination with the image. This research used a classroom action design by conducting two cycles and each cycle consisted of two sessions. This research used a classroom action design by conducting two cycles and each cycle consisted of two sessions. This research was conducted in two cycles and each cycle consisted of two sessions. The research conducted pre-test, post-test, and questionnaires to collect the data before analyzing it. The results of the research showed that there was a significant improvement in the subjects' performance in the pre-and post-test. From the questionnaire conducted in the last cycle, the students received a positive response regarding their changing learning behavior in relation to the application of the KWL strategy. Based on the findings of the study, the students' reading comprehension can be improved by using the KWL strategy in combination with an image.